Preferential apical infection of Caco-2 intestinal cell monolayers by SARS-CoV-2 is associated with damage to cellular barrier integrity: Implications for the pathophysiology of COVID-19 - Clémence Garrec; Jeffrey Arrindell; Jonatane Andrieu; Benoit Desnues; Jean-Louis Mege; Ikram Omar Osman; Christian Devaux (PLoS ONE, 2025)
SARS-CoV-2 can infect different organs, including the intestine. In an in vitro model of Caco-2 intestinal cell line, we previously found that SARS-CoV-2 modulates the ACE2 receptor expression and affects the expression of molecules involved in intercellular junctions. To further explore the possibility that the intestinal epithelium can serve as an alternative infection route for SARS-CoV-2, we used a model of polarized monolayers of Caco-2 cells (or co-cultures of two intestinal cell lines: Caco-2 and HT29) grown on the polycarbonate membrane of Transwell inserts, inoculated with the virus either in the upper or lower chamber of culture to determine the tropism of the virus for the apical or basolateral pole of these cells. In both polarized Caco-2 cell monolayers and co-culture Caco-2/HT29 cell monolayer, apical SARS-CoV-2 inoculation was found to be much more effective in establishing infection than basolateral inoculation. In addition, apical SARS-CoV-2 infection triggers monolayer degeneration, as shown by histological examination, measurement of trans-epithelial electrical resistance, and cell adhesion molecule expression. During apical infection, the infectious viruses reach the lower chamber, suggesting either a transcytosis mechanism from the apical side to the basolateral side of cells, a paracellular trafficking of the virus after damage to intercellular junctions in the epithelial barrier, or both. Taken together, these data indicate a preferential tropism of SARS-CoV-2 for the apical pole of the human intestinal tract and suggest that infection via the intestinal lumen leads to a systemic infection.